Magnetic graphene oxide modified by imidazole‐based ionic liquids for the magnetic‐based solid‐phase extraction of polysaccharides from brown alga. Issue 16 (31st July 2017) - Wang, Xiaoqin; Li, Guizhen; Row, Kyung Ho
Abstract : Magnetic graphene oxide was modified by four imidazole‐based ionic liquids to synthesize materials for the extraction of polysaccharides by magnetic solid‐phase extraction. Fucoidan and laminarin were chosen as the representative polysaccharides owing to their excellent pharmaceutical value and availability. Fourier transform infrared spectroscopy, field‐emission scanning electron microscopy, and thermogravimetric analysis were applied to characterize the synthesized materials. Single‐factor experiments showed that the extraction efficiency of polysaccharides was affected by the amount of ionic liquids for modification, solid–liquid ratio of brown alga and ethanol, the stirring time of brown alga and ionic liquid‐modified magnetic graphene oxide materials, and amount of 1‐(3‐aminopropyl)imidazole chloride modified magnetic graphene oxide materials added to the brown alga sample solution. The results indicated that 1‐(3‐aminopropyl)imidazole chloride modified magnetic graphene oxide possessed better extraction ability than graphene oxide, magnetic graphene oxide, and other three ionic‐liquid‐modified magnetic graphene oxide materials. The highest extraction recoveries of fucoidan and laminarin extracted by 1‐(3‐aminopropyl)imidazole chloride modified magnetic graphene oxide were 93.3 and 87.2%, respectively. In addition, solid materials could be separated and reused easily owing to their magnetic properties.